A View from the Edge: A Teacher’s Perspective on Citizen Science - Lindsey, Ed (Maine Policy Review, 2017)
Old Town High School teacher Ed Lindsey examines the benefits of engaging high school students in citizen science, based on his experience collecting stream organisms and analyzing the level of mercury in their bodies.